MICROBIOLOGICAL AND PHYSICAL PROPERTIES OF BEEF MARINATED WITH GARLIC JUICE - Nurwantoro, N.; Bintoro, V.P.; Legowo, A.M.; Ambara, L.D.; Prakoso, A.; Mulyani, S.; Purnomoadi, A. (Journal of the Indonesian Tropical Animal Agriculture, 2011)
The study was carried out to investigate the effect of marination, performed by soaking of beef ingarlic juice, on microbiological and physical properties. The study was committed to a completelyrandomized design, with 5 treatments, i.e.: T0 (unmarinated beef, as a control), T1, T2, T3, and T4 thatbeef were marinated in garlic juice for 5, 10, 15, and 20 minutes, respectively, at room temperature(25⁰C). Each treatment consisted of 4 replications. Examination upon experimental parameters wasconducted after marinated (and control) beef was stored for 8 hours at room temperature. Total bacteria,total coliform and water holding capacity of beef were significantly (P<0.05) affected by marinationwith garlic juice. Conversely, cooking loss was not significantly affected (P>0.05) by the treatments. Asa conclusion, marination of beef with garlic juice could reduce total bacteria, total coliform, and waterholding capacity, but could not reduce cooking loss.